Market Access and Removal of Quantitative Restrictions: Perception of Farmers in Haryana - Chand, Suhhash (Gyan Management Journal, 2008)
The WTO Agreement on Agriculture (AOA) formalized at the end of Uruguay round of negotiations aims to remove trade distorting practices and to facilitate a fair and market-oriented agricultural trading systein. The agreement calls for tariffication of all non-tariff barriers, open domestic market to imports, and to reduce the support and protection to agriculture in developed and developing countries. Restrictions on market access may be in the form of quantitative restrictions ( quota, import restrictions through permits, import licensing etc.). All these measures can be discretionary and can effectively impede trade. In the AOA it was decided that all member countries would lift quantitative restrictions on their imports under a time bound programme and convert all non-tariff barriers into equivalent tariff barriers.
Keywords: Market Access; Removal of Quantitative Restrictions; Farmers in Haryana